Empowering Parental Involvement In Fostering Children's Independence During The Transition From Kindergarten To Primary School - Atmari; Sabilillah, Faris Daffa; Azkiya, Aflah Naila; Putri, Dina Awalia; Aisyah, Edty Meita; Amaliyah, Nabilah (LPPM, STAI Al-Azhar Menganti, 2024)
Parenting assistance aims to increase parents' understanding and skills in educating children. So that children's independence in dealing with situations or completing a task without depending on other people can be formed. The research method used is the ABCD (Asset Based Community Development) method. This method is an approach to community development. There are 5 procedures used in the ABCD method, namely Define, Discovery, Dream, Design, and Deliver/destiny. This parenting assistance program can be implemented well and optimally. The research results show that the parenting assistance that has been carried out has had a positive impact in overcoming various problems in educating children in Plabuhanrejo village, Mantup, Lamongan. Sooko, whose knowledge about parenting in society was initially still relatively low, is increasingly increasing. As well as the growing sense of independence in children, who initially were still dependent on their parents, are now more independent in doing things.